Innovation in Mathematics Education through Lesson Study: Challenges to STEM on Statistics and Electricity Saving - Riyanta Riyanta; Ika Wulandari (SEAMEO Regional Centre for QITEP in Mathematics, 2017)
This collaborative research aims to provide necessary scientific and practical knowledge on statistics and electricity saving topics through integration of energy efficiency into vocational schools’ mathematics curriculum. The paper reports on how the teachers in a lesson study group developed teaching and learning models on statistics integrated with electricity saving. The implementation processes of this learning model started with data collection, continued with data processing, data presentation, and data analysis of the electricity billing payment of the students’ houses. Through this learning process, the students were expected to be more aware in saving electricity and using energy wiser. The analyses were done qualitatively using triangulation including combining documents, observations, photographs, and videos.The findings revealed that this learning model sharpened the students’ ability around reasoning, processing, presenting and analyzing the data from contextual problems. Students could also define the factors affecting the electricity used, and then identify the ways to save energy. Further, the students created a simple video and poster for a saving electricity campaign at school, home, and social media. While the results are interesting and encouraging and provide some promising directions, they are not a proof and a much larger study would be needed to determine if the results are due to the approach or due to the teachers’ enthusiasm, novelty effect or what is known as the Hawthorne Effect.